Annotated record of the detailed examination of Mn deposits from DSDP Leg 65 (Holes 482, 482A, 482B) - Brian T R Lewis; Paul T Robinson (PANGAEA, 1983)
Deep Sea Drilling Project (DSDP) Legs 64 and 65 were planned as a coordinated drilling investigation of the Gulf of California. The primary goals of Leg 64 were to investigate the early evolution of a passive continental margin and to study hydrothermal systems in the Guaymas Basin. Leg 65 was designed to study the processes of crustal accretion along the relatively fastspreading East Pacific Rise for comparison with the slow-spreading Mid-Atlantic Ridge. It was planned to drill a transect across the East Pacific Rise just south of the Tamayo Fracture Zone and to penetrate deep into the crust at one site near the ridge crest. The purpose was to sample crustal sections formed at a relatively fast spreading ridge in order to investigate the processes of crustal accretion in this environment.